Increasing Understanding of Research and Community Service Methods Through Webinars - Iswadi, Iswadi; Anom, Erman; Tamzil, Fachmi (Universitas Ahmad Dahlan, 2023)
Background: Insight and activeness to carry out research are things that must be owned by many people, organizations, as well as agencies and institutions, if they want conditions changes to occur in the environment that they want. Research helps to produce better changes with various methods or approaches. The college as the birthplace of reliable researches must be able the entire academic community in it to have insight into research methodology in order to increase community service. Contribution: This research was conducted to explain the implementation of webinar in order to increase the understanding and mastery of the academic community from lectures, students, and the public in general regarding research methodology. Method: The methodology used is qualitative descriptive. Results: The results showed that the holding of the webinar activity